1998
DOI: 10.1073/pnas.95.4.1534
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoresis in lyotropic polymer liquid crystals

Abstract: Excellent electrophoretic separations of a variety of biological molecules can be accomplished by using uncharged, triblock copolymers as the ''gel'' media. These copolymers form uncrosslinked, lyotropic liquid crystalline phases of large micelles between which molecules must travel. Unlike crosslinked hydrogels in common use, these alternative media have highly ordered internal structures. Pluronic F127, representative of the copolymer class, contains poly(ethylene oxide) (EO) and poly(propylene oxide) (PO) u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
97
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(103 citation statements)
references
References 32 publications
6
97
0
Order By: Relevance
“…The consequent gelation of Pluronic by hierarchical selfassembly is maintained in the presence of both unbound and Pluronic-conjugated proteins. If, under the current synthetic conditions, the micelles in the amphiphilic Pluronic block copolymers self-assemble into hierarchical architectures, [34][35][36] they could presumably act in a manner similar to that of the mms6-containing bacterial phospholipid membranes, allowing a surfacecontrolled crystal growth. Both unbound forms of mms6 are likely to phase-separate from the gel into the water-rich regions of the gels, being expelled from the micelles.…”
Section: Resultsmentioning
confidence: 99%
“…The consequent gelation of Pluronic by hierarchical selfassembly is maintained in the presence of both unbound and Pluronic-conjugated proteins. If, under the current synthetic conditions, the micelles in the amphiphilic Pluronic block copolymers self-assemble into hierarchical architectures, [34][35][36] they could presumably act in a manner similar to that of the mms6-containing bacterial phospholipid membranes, allowing a surfacecontrolled crystal growth. Both unbound forms of mms6 are likely to phase-separate from the gel into the water-rich regions of the gels, being expelled from the micelles.…”
Section: Resultsmentioning
confidence: 99%
“…Pluronic copolymers possess a unique viscosity-adjustable property, which renders PF127 gels easy to handle compared to conventional crosslinked hydrogels based on, amongst others, poly(vinyl alcohol), gelatin, and poly (N-isopropylacrylamide). [36,37] As an example, PF127 aqueous solutions (18-30% (w/v)) appear to be fluid at low temperatures (0-5 8C), and can transform into a gel-like cubic liquid crystal within a few seconds when heated. [38][39][40] Such a fast sol-gel transition renders PF127 gels particularly useful as an injectable vehicle for local delivery of various therapeutic agents.…”
mentioning
confidence: 99%
“…In comparison, SPEL features a temperature-dependant reversible sol-gel transition. Since this transition temperature can be adjusted by varying the concentration of PF127, [36,37] it is possible to apply SPEL as an injectable drug-delivery system for magnetically modulated release of hydrophobic bioactive agents on pathological sites.…”
mentioning
confidence: 99%
“…Indeed, no major improvements in either sequencing readlength or elution times have been reported that can be directly related to a revolution in sieving matrices. We must add, however, that in some cases, the separation process is probably novel and remains to be investigated [3,4].…”
Section: Introductionmentioning
confidence: 99%